Response of cucumber to target spot as a function of plant age - Da Silva, Lucas Meleiro; De Arruda, Maria Cecília; Santo Dadazio, Taís; Firmino, Ana Carolina [UNESP]; Fischer, Ivan Herman (Lepidus Tecnologia, 2023)
The target spot of cucurbits, caused by Corynespora cassiicola, occurs in several cultivated species, being considered an important disease on cucumbers. The objetive was to determine the cucumber response to the target leaf spot as a function of plant age, seeking a better understanding of the pathosystem in order to avoid economic damages to producers. Cucumber 'Soldier' plants were inoculated at 20, 30 and 40 days after sowing. Disease severity was evaluated at three, six and nine days after inoculation of the pathogen; the number of leaves and plant height at intervals of 7 to 10 days after inoculation of the pathogen; the number and fresh mass of fruits and the fresh and dry mass of the aerial parts of the plants at 60 days after sowing. A lower disease severity was observed on younger leaves, on plants inoculated at 20 days of age from the sixth day of evaluation, with plants inoculated at 30 days being the most susceptible, reaching 64% disease severity after nine days of inoculation. The variables plant height, number of leaves and fruits, fruit production and fresh and dry mass of the aerial part of the plant were significantly affected by the age of the plant at the time of inoculation of the pathogen C. cassiicola, with the lowest values, in general, in the youngest inoculated plants, at 20 days, while the 40-day-old plants had the least affected vegetative development and production, evidencing the importance of delaying the entry of the disease in the area.
Keywords: Corynespora cassiicola; Cucumis sativus; Phenological stage